ChemInform Abstract: Continuous Flow Synthesis of α‐Halo Ketones: Essential Building Blocks of Antiretroviral Agents. Issue 30 (29th July 2014) - Pinho, Vagner D.; Gutmann, Bernhard; Miranda, Leandro S. M.; de Souza, Rodrigo O. M. A.; Kappe, C. Oliver
Abstract A highly efficient continuous flow process for the synthesis of α‐halo ketones is reported.